Analysis of Cerebral Blood Flow Entropy While Listening to Music with Emotional Content - Chacon-Pacheco, M; Jara-Valencia, J; Landerretche-Sotomayor, J; Cavieres-Carvajal, R (IOP Publishing Ltd, 2021)
Objective. Music is one of the most sublime stimuli that human beings can experience. Despite being just an acoustic wave that exerts little physical influence on a subject, it triggers profound changes in emotions and physiological states. This study explores the possibility of detecting subtle changes in cerebral blood flow velocity in response to emotional reactions produced by different musical stimuli using multiscale entropy analysis. Approach. Cerebral blood flow signals were successfully recorded for 16 subjects while performing five different musical tasks. The entropy of each signal was estimated using multiscale sample entropy. Main results. This method has been shown to be capable of revealing the complexity of the internal dynamics of different physiological systems, which cannot be appreciated with classic approaches based on entropy on a single scale. Significance. Significant differences in entropy were found between two of the tasks, which suggests that intense cognitive activities with emotional content cause a decrease in the entropy of cerebral haemodynamics. © 2021 Institute of Physics and Engineering in Medicine.
Keywords: multiscale entropy; music; sample entropy; cerebral blood flow; haemodynamics